Corporate Governance, Financial Characteristics, Macroeconomic Factors and Financial Performance of Agricultural Firms Listed at the Nairobi Securities Exchange, Kenya - Aluoch, Moses Odhiambo (European Scientific Journal, ESJ, 2021)
This study sought to examine the relationships between corporate governance, financial characteristics, macroeconomic factors and financial performance of agricultural firms listed at the Nairobi Securities Exchange, Kenya. The specific objectives were to establish the effect of corporate governance on financial performance; to determine the intervening effect of financial characteristics on corporate governance and financial performance; to establish the moderating effect of macroeconomic factors on corporate governance and financial performance of listed agricultural firms; and to establish the joint effect of corporate governance, financial characteristics, macroeconomic factors and financial performance of listed agricultural firms in Kenya. This study is anchored on agency theory, transaction cost theory; political theory and cash conversion cycle theory. The study used census approach and a target population of seven agricultural firms listed at the Nairobi Securities Exchange between 2002 and 2016 was incorporated. The study used panel data. Corporate governance, financial characteristics and financial performance data was extracted from annual reports of the individuals firms while macroeconomic factors data was extracted from Central Bank of Kenya and Kenya National Bureau of Statistics economic reports. The study employed longitudinal descriptive research design. Descriptive and panel data regression analysis were conducted. Corporate governance had significant effect on financial performance of listed agricultural firms in Kenya; the intervening effect of financial characteristics on the relationship between corporate governance and financial performance was not determined; the moderating effect of macroeconomic factors on the relationship between corporate governance and financial performance was confirmed; and the joint relationship between corporate governance, financial characteristics and macroeconomic factors on financial performance was established. The study recommended a review of corporate governance principles and directors to comply with corporate governance structure and practices to enhance financial performance of firms.